Effects of the stator design parameters on the torque performance of a PMaSynRM - Tap, Alper; Xheladini, Liridon; Imeryuz, Murat; Yilmaz, Murat; Ergene, Lale T. (IEEE, 2017)
In this paper, the effects of the stator design parameters on the torque and torque ripple of a Permanent Magnet Assisted Synchronous Reluctance Motor (PMaSynRM) is searched. As the rotor design parameters has very important role in the torque production dramatically, a fixed rotor structure is used as base design and kept constant throughout the paper to observe and compare the effects of stator structural or winding changes. First step is to investigate the effects of stator slot number for the same number of the pole. Different winding schemes such as distributed, concentric, single layer, double layer configurations are studied to reach a better stator design. As a final step, optimizations on stator slot shapes, slot openings, teeth bottom geometries and air gap length are carried out and all the results are presented.